EKSPLORASI KESEMPATAN UNTUK MELAKUKAN FRAUD DI PEMERINTAH DAERAH, INDONESIA (EXPLORATION OPPORTUNITIES TO COMMIT FRAUD IN LOCAL GOVERNMENTS, INDONESIA) - Maria, Evi; Halim, Abdul; Suwardi, Eko; Miharjo, Setiyono (UI Scholars Hub, 2019)
This study aims to explore the opportunity factors to commit fraud in local governments, Indonesia. The study samples were 785 local governments in Indonesia that had been audited by the Audit Board of the Republic of Indonesia in 2012 and 2013 fiscal years. Data were analyzed using factor analysis and logistic regression analysis. This study found that the opportunity to commit fraud in local governments, Indonesia could be measured using sub-districts, total assets, population, and capital expenditure variables. Additional test results found opportunity factor statistically significant affected the probability of fraud cases in local governments, Indonesia. This research only focuses on exploring the opportunity factor for fraud, in terms of ineffective monitoring and has not explored the opportunity factors that encourage fraud in terms of industrial nature and organizational structure